PENGARUH BRAND AWARENESS, BRAND ASSOCIATION DAN ADVERTISING EFFECTIVENESS TERHADAP KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE SAMSUNG (STUDI KASUS MAHASISWA S1 UNIVERSITAS DIPONEGORO) - Amelina Darayani; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2016)
In the globalization era, smartphones industries are the most developed industry in Indonesia. This situation create business competition are increasingly competitive. One of the signs of market competitiveness can be seen in the last few years on how there’s declining on market share and selling volume of Samsung Smartphone products in Indonesia. While the purpose of this research is to explain and elaborate the power of brand awareness, brand association and advertising effectiveness in influencing University of Diponegoro students decision to buy Samsung Smartphone products.The result of this research demonstrates that the variable of brand awareness have significant and positive impact toward purchasing decisions; the variable of brand association have significant and positive impact toward purchasing decisions and the variable of advertising effectiveness have significant and positive impact toward purchasing decisions.The conclusion from this research is that samsung’s smartphone products are perceived well in all the three variables (brand awareness, brand association and advertising effectiveness). While suggestion that can be presented from this research is it’s necessary for Samsung to build brand awareness and a better brand association if they want to mantain and gain their product sale in order to improve the company's image, thus making it easier for consumers in making purchasing decisions.